International capital mobility: a re-visit of Feldstein-Horioka puzzle - Hassan, Ibrahim Bakari; Mohamed, Azali (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper investigates the status of international capital mobility by reexamining the Felstein-Horioka (1980) puzzle. Data on savings and investment of 51 high-income countries were analyzed using System-GMM of Arellano and Bovver (1995)/ Blundell and Bond (1998). The β of a saving-retention coefficient of the System-GMM reads 0.17 signifying low correlation between the saving and the investment. Contrary to the Felstein-Horioka findings, the result suggests high capital mobility across high-income economies. The study further recommends acknowledging the increasing interrelations among countries in modeling international capital mobility.